2011
DOI: 10.1590/s0103-166x2011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da estratégia saúde da família a partir das crenças dos profissionais

Abstract: As pesquisas de avaliação da Estratégia Saúde da Família funcionam como ferramenta de feedback nas decisões de seus gestores. Assim, o presente estudo objetivou avaliá-la a partir das crenças dos seus profissionais. Uma amostra probabilística de 337 profissionais respondeu à "Escala de Avaliação da Estratégia Saúde da Família pelos Profissionais", que investiga os seguintes fatores: 1) Recursos materiais (α=0,86); 2) Eficiência no atendimento (α=0,80); e 3) Infraestrutura física (α=0,73). Os resultados apresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 3 publications
1
13
0
8
Order By: Relevance
“…The FHS was ranked better overall and attained higher indexes only for four out of the eight attributes. These findings are in line with results of other investigations showing superior performance of the FHS on evaluation by health professionals or users 8,10,[12][13][14]23,24 . The performance of PHC as assessed by managers and health professionals could not be directly compared.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The FHS was ranked better overall and attained higher indexes only for four out of the eight attributes. These findings are in line with results of other investigations showing superior performance of the FHS on evaluation by health professionals or users 8,10,[12][13][14]23,24 . The performance of PHC as assessed by managers and health professionals could not be directly compared.…”
Section: Discussionsupporting
confidence: 92%
“…Efforts towards training health professionals of the FHS model, particularly health assistants, have been made by the Brazilian Ministry of Health 8 , perhaps explaining the differences observed in evaluations of this attribute by health assistants relative to general practitioners and nurses. Additionally, CHW is a category existing only in the FHS, and they are often responsible for facilitating contact and communication with families, providing information on risk factors, as well as health and social problems of their members 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship with the health team is paramount to establish favorable conditions for the involvement of the patient with their health problems; the contract of establishment in which are explicit rights and duties of both the patient and the professional can be a good strategy to do so. A study (16) which analyzed the efficiency of the care of the Family Health Strategy from beliefs of professionals showed that 53.4% rated the service negatively, emphasizing the need to modify or eliminate barriers in order to improve the conditions of service for its users.…”
Section: Discussionmentioning
confidence: 99%